Implementation and Effectiveness of the Think Pair Share Cooperative Learning Method in Fiqh Teaching: An Analysis at MTs Nurul Islam, Kuala District - Bakti, Surya; Yusuf, Muhammad; Dea, Dea (Jurnal Pendidikan Islam, 2023)
Purpose – This research aims to evaluate the effectiveness of the Think Pair Share (TPS) learning method in the context of Fiqh education at MTs Nurul Islam, Kuala District, focusing on enhancing student participation and understanding and overcoming challenges in conventional learning. Design/methods/approach – Employing qualitative approaches and field research, this study gathered data from school principals, teachers, and students using structured interviews, observations, and documentation. The data analysis process was carried out qualitatively and descriptively, focusing on the reduction, presentation, and conclusion of relevant data. Findings – The research findings indicate that applying the TPS method has improved student engagement in the Fiqh learning process. This method facilitated more interactive and collaborative learning, reduced monotony, and developed critical and creative thinking skills. Challenges encountered include a lack of active student participation and group management issues, which can be addressed by adjusting teaching materials and adopting more heterogeneous learning strategies. Research implications – These findings provide new insights into the benefits of using innovative methods like TPS in Fiqh education. They emphasize the importance of further teacher training in innovative learning methods to improve the quality of Islamic education in Indonesia. This study also has implications for developing more effective learning strategies in various educational contexts.